Adjuvant Zinc Therapy in Young Infants with Sepsis: A Systematic Review - Enayet Badhan, Raisa; Alam, Md Jahangir (Medicine Today, 2025)
Introduction: Two of the main risk factors for neonatal sepsis are prematurity and low birth weight. Previous researches demonstrated the advantages of zinc supplementation for small-for-gestational age delivery outcomes and during pregnancy. However, there is little data on the possible advantages of supplementing with zinc to cure or prevent serious infections in this age group. Aim of this review is to evaluate the effectiveness of zinc supplementation as a preventative and therapeutic measure in young infants with sepsis. Materials and Methods: PubMed, Elsevier Science Direct, Google Scholar, MEDLINE, Cochrane CENTRAL, and additional databases were searched for articles to be reviewed. Included studies were evaluated the effects of therapeutic and preventive zinc supplementation in young infants in relation to the incidence and results of suspected sepsis. Seven randomized controlled trials involving 2,081 infants were included. Results: Certain research indicates that zinc supplementation may have a protective effect on the neonatal mortality rate (NMR) of preterm newborns, but it has no influence on the incidence of sepsis. Therapeutic zinc was linked to a considerable decrease in treatment failure in young newborns. There was no discernible impact of therapeutic zinc supplementation on hospital stay or NMR in newborns. Conclusion: Supplementing with zinc has no significant effect on hospital stay or sepsis prevention, however it may lower mortality and treatment failure in early newborns. Larger sample numbers and additional research are required to determine the direction and extent of any impacts. Medicine Today 2025, Vol.37 (1): 149-153